2015
DOI: 10.1038/srep17746
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal caffeine exposure induces a poor quality of articular cartilage in male adult offspring rats via cholesterol accumulation in cartilage

Abstract: Epidemiological investigations indicate that osteoarthritis is associated with intrauterine growth retardation (IUGR) and abnormal cholesterol metabolism. Our previous studies showed that prenatal caffeine exposure (PCE) induced chondrogenesis retardation in IUGR offspring rats. The current study sought to investigate the effects of PCE on male IUGR offspring rats’ articular cartilage, and the mechanisms associated with abnormal cholesterol metabolism. Based on the results from both male fetal and adult fed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 57 publications
(76 reference statements)
1
34
0
Order By: Relevance
“…PCE can increase the susceptibility to osteoarthritis in adult rat offspring and that its mechanism was related to the accumulation of localized cholesterol in the articular cartilage (43). Taken together, these studies suggest that PCE can induce hypercholesterolemia in adult rat offspring and increase the risk of multiple metabolic diseases (e.g., cardiovascular disease and osteoarthritis).…”
Section: Pce Induces Hypercholesterolemia and Increases The Risk Of Mmentioning
confidence: 74%
See 1 more Smart Citation
“…PCE can increase the susceptibility to osteoarthritis in adult rat offspring and that its mechanism was related to the accumulation of localized cholesterol in the articular cartilage (43). Taken together, these studies suggest that PCE can induce hypercholesterolemia in adult rat offspring and increase the risk of multiple metabolic diseases (e.g., cardiovascular disease and osteoarthritis).…”
Section: Pce Induces Hypercholesterolemia and Increases The Risk Of Mmentioning
confidence: 74%
“…Our previous studies have confirmed that with overexposure to maternal GCs induced by PCE, multiple organs of fetal rats appeared to be structurally and functionally different during development. The liver, as one of those important organs, had enhanced TG synthesis (10), whereas secondary organs (e.g., articular cartilage and kidney) exhibited varying degrees of developmental inhibition and dysfunction (43,54). In this study, we confirmed that the liver had enhanced cholesterol synthesis function under high levels of maternal GCs, which is the specific manifestation of the thrifty phenotype in the fetal liver and constitutes the pathophysiological basis of susceptibility to hypercholesterolemia and related metabolic diseases in adult offspring.…”
Section: Maternal Gc Overexposure Induced Programming Alterations In mentioning
confidence: 99%
“…Caffeine (1,3,7-trimethylxanthine) is a natural alkaloid belonging to the family of methylxantines [23][24][25][26][27][28][29][30][31]. The main caffeine sources are tea leaves, cola nuts, and coffee and cocoa beans [23][24][25][26][27][28][29][30][31][32].…”
Section: Caffeinementioning
confidence: 99%
“…Nonetheless, it is among the most frequently consumed substances, with an average daily ingestion of 120 mg [23][24][25][26][27][28][29][30][31][32]. It is present in beverages (e.g., coffee, tea, soft drinks, and energy drinks), food (e.g., cocoa and chocolate) [23][24][25][26][27][28][29][30][31][32], and some stimulants and is used as an adjuvant to increase the absorption of some medications [23][24][25][26][27][28][29][30][31]. Studies show that coffee (60%-75%) and tea (15%-30%) are the main sources of caffeine for adults, while among children, chocolate and soft drinks are the major intake sources [30][31][32] (Figure 3).…”
Section: Caffeinementioning
confidence: 99%
See 1 more Smart Citation